Autographs don't burn : letters to the Bunins. - Bunin, Ivan Alekseevich, 1870-1953 (Academic Studies Press, 2020)
"This book sprang from three handwritten lines by Ivan Bunin, Russia's first winner of the Nobel Prize for Literature. Found inside a first edition of Mitya's Love, they led to the discovery of one of the largest corpora of letters written to Ivan and Vera Bunin by two people whose lives and legacy had been, until now, forgotten. These letters are now in the Russian Archive in Leeds (RAL), and are published here for the first time. The book also focuses on memory and history in its purest form, as narrated by witnesses who lived through the most tragic century in Russian history. Their stories involve Grand Dukes, Russian literary and political giants, as well as one of the architects of the Gulag, and show how these lives intertwined. It also sheds new light on the life and works of Chekhov, Gorky, A. Tolstoy, and Bunin"--